PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN SAHAM SYARIAH TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) PERIODE 2020-2023 - Alam Wiku Dananjaya; Imron Rosyadi (JURNAL LENTERA BISNIS, 2025)
This research seeks to examine how profitability, liquidity, leverage, and dividend policy influence a company's value. A quantitative approach is employed as the research methodology. The study focuses on sharia-compliant stocks listed on the Jakarta Islamic Index (JII) between 2020 and 2023. A purposive sampling method was utilized, resulting in a total sample of 108 sharia stocks. Data analysis was conducted using the SPSS software. The findings indicate that profitability, liquidity, and leverage each have a significant impact on company value, whereas dividend policy does not contribute to changes in company value.